Successful treatment of psychosis in dentatorubral‐pallidoluysian atrophy with quetiapine: A case report - Zui Narita; Tomiki Sumiyoshi (Wiley, 2018)
Abstract Introduction Patients with dentatorubral‐pallidoluysian atrophy (DRPLA) sometimes elicit psychosis. First‐generation antipsychotic drugs have been reported to be effective in treating psychotic symptoms associated with the disease. However, little information is available on the benefits of second‐generation antipsychotic drugs (SGAs). Case We report on a 47‐year‐old man with DRPLA whose psychotic symptoms were effectively treated with quetiapine, one of the SGAs. He suffered from delusions, auditory hallucinations, and disorganized speech. Initially, other antipsychotic drugs were tried, but were withdrawn because of adverse effects before switching to quetiapine. Conclusion Our observations add to the notion that some of the SGAs are useful for ameliorating psychosis in DRPLA.